2020
DOI: 10.21873/anticanres.14553
|View full text |Cite
|
Sign up to set email alerts
|

DRAQ7 as an Alternative to MTT Assay for Measuring Viability of Glioma Cells Treated With Polyphenols

Abstract: Background/Aim-The tetrazolium-based MTT cytotoxicity assay is well established for screening putative anti-cancer agents. However, it has limitations including lack of reproducibility with glioma cells treated with polyphenols. The aim of this study was to evaluate whether a flow cytometric assay with the anthraquinone, DRAQ7, was a better alternative than the colorimetric MTT assay for measuring cell viability.Materials and Methods-Two glioma cell lines (IPSB-18, U373) and 1 pancreatic cancer cell line (AsPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To quantify cell death, the cells were stained with DRAQ7, a membrane-impermeable dye that stains the double-stranded DNA of dead cells. 42 The cells were cultured for 3 days in the presence or absence of the degradation products digested with PK. By studying cell toxicity, we found that the degradation products of either uncrosslinked or crosslinked scaffolds did not affect the cell number or cell death in human dermal fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify cell death, the cells were stained with DRAQ7, a membrane-impermeable dye that stains the double-stranded DNA of dead cells. 42 The cells were cultured for 3 days in the presence or absence of the degradation products digested with PK. By studying cell toxicity, we found that the degradation products of either uncrosslinked or crosslinked scaffolds did not affect the cell number or cell death in human dermal fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glioma is a primary intracranial tumor with high incidence and high degree of malignancy, and the average survival time of patients is relatively short [12]. Rab23 gene is closely related to the progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The co-delivery complexes have been well characterized in terms of pDNA CC, shape, mean size, surface charges and biocompatibility At this stage, we must also mention that the cellular viability data, presented in Figure 4, does not fully correlate with both the quantified p53 levels (Table 2) and the observed caspase-3 activity in HeLa cells. For this discrepancy can, probably, contribute the most common reported limitations of MTT assay, such as, lack of sensitivity, interference with cell culture medium and overestimation of cell viability [63,64].…”
Section: Discussionmentioning
confidence: 99%